2020
DOI: 10.46827/ejes.v7i7.3149
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of University Students’ Response in Times of Pandemic Crisis (Covid-19)

Abstract: <p>In response to the need for more research evidence, as an empirical base for discussion on the experiences of young people, the current study aims to contribute to the discussion on their attitudes and behaviors in times of pandemic crisis. It is of great importance, that under the pressure of social limits on social distancing for the novel Coronavirus (COVID-19), young students have to adapt more efficiently with new technologies both every day and for educational practices, where their experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 3 publications
8
52
0
5
Order By: Relevance
“…As far as the students' academic life is concerned, we were interested in: (1) the availability of different kinds of home infrastructure needed to ensure efficient study; and (2) the students' selfreported computer skills. Both issues were also mentioned by Kamarianos et al [25], Sahu [44] and Baticulon et al [55]. When examining the potential impact of the COVID-19 outbreak on the education of the students in our study on the global level, the share of students with frequent access to specific equipment was highest for office supplies, e.g.…”
Section: Academic Lifesupporting
confidence: 66%
See 1 more Smart Citation
“…As far as the students' academic life is concerned, we were interested in: (1) the availability of different kinds of home infrastructure needed to ensure efficient study; and (2) the students' selfreported computer skills. Both issues were also mentioned by Kamarianos et al [25], Sahu [44] and Baticulon et al [55]. When examining the potential impact of the COVID-19 outbreak on the education of the students in our study on the global level, the share of students with frequent access to specific equipment was highest for office supplies, e.g.…”
Section: Academic Lifesupporting
confidence: 66%
“…the switch to online lectures/tutorials, closed libraries, changed communication channels for teachers' and administrative support, new assessment methods, different workloads and performance levels etc.) [7,12,15,[21][22][23][24][25][26][27] and social life (closed dorms and therefore moving back home, no meetings with friends, university colleagues or relatives, no parties, no traveling, remaining trapped abroad etc.) [7,13,[29][30][31], as well as their personal financial situation (loss of student job, worries about their own financial situation, future education and career) [14,32,33] and emotional health (fears, frustrations, anxiety, anger, boredom etc.)…”
Section: Introductionmentioning
confidence: 99%
“…As far as the students' academic life is concerned, we were interested in (1) the availability of different kinds of home infrastructure needed for efficient study, and (2) the self-report of students' computer skills. Both challenges were mentioned also by Kamarianos et al [25], Sahu [44], and Baticulon et al [55]. When examining the potential impact of the COVID-19 outbreak on the education of students, in our study, on a global level, the share of students with frequent access to the specific equipment was highest for office supplies, e.g.…”
Section: Academic Lifesupporting
confidence: 65%
“…The students were most satisfied with real-time video conferences, video recordings and written communication with Oceania and Europe as global frontrunners while developing countries (from Asia and Africa) significantly lagged behind. The study of Kamarianos et al [25] also confirmed that in a given situation, being a student (Generation Z), thus digitally much more literate than previous generations, helped a lot to overcome the difficulties of the transition from onsite to online learning. There was not much time to prepare in order to reorganize the teaching and learning processes -this transition had to be quick and efficient [44].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation